دور التحرر المالي في تعزيز الابداع المالي : دراسة تحليلية نظرية - زهراء صالح الخياط (PROSPECTIVE RESEARCHES, 2023)
This research aims at clarifying the role which financial liberation plays in enhancing and motivating the financial innovation and that is by liberating the rules which govern the financial market and instrument; in addition to liberalizing interest rate for its effect in improving the ability of the financial and banking system, leading to the improvement of its role and leaving the guidance of credit. This is supposed to be done in a gradual way. This has been done in some Arabic countries. It was concluded that financial liberation has led to enhancing and developing the financial system by introducing it in to a wide perfect collection of financial products, besides, it increases the flexibility of financial and banking institutions in creating assurance and investment. While the financial innovation includes invention and updating new financial tools like the financial derivatives which include swaps, options and futures. The research has reached them for the necessity of liberating the financial and banking sector for the sight of progress extent and getting benefit of financial creativity.